ANALYSIS OF TEACHER PERFORMANCE IN TERMS OF WORK MOTIVATION AND IMPLEMENTATION OF ACADEMIC SUPERVISION IN TK NEGERI KAMPUNG RAKYAT DISTRICT, SOUTH LABUHANBATU REGENCY - Desi Murniati Siregar; Aman Simare-mare; Yasaratodo Wau (Sensei International Journal of Education and Linguistic, 2022)
This study aims to determine and analyze in depth the academic performance of the supervision carried out by the principal in improving the performance of teachers at the State Kindergarten in the Kampung Rakyat District. The research method uses qualitative data collection techniques, observations, interviews and conclusions. The results of the research Planning for academic supervision by the principal at the Kampung Rakyat State Kindergarten can be well structured. It can be seen that the supervision planning starts from compiling a supervision schedule, determining the purpose of supervision, implementing supervision, the techniques needed, the instruments to be used, and important things that support the implementation of good supervision. Giving motivation to teachers is able to provide encouragement to improve teacher performance. The role of the principal in fostering teacher work motivation by carrying out academic supervision. The implementation of academic supervision by the principal is carried out according to the planning stages of academic supervision and takes a humanist approach that creates comfort for teachers, even the teacher is used as a friend to discuss and agree on the implementation of follow-up supervision of academic supervision starting from face-to-face direct coaching, evaluation, and analyze and process the results of the evaluation which in the end prepare a follow-up report and carry out the follow-up. In connection there are principals who find teachers who have difficulty in carrying out learning evaluations, the principals try to overcome them.